2007
DOI: 10.1002/jgt.20250
|View full text |Cite
|
Sign up to set email alerts
|

Hamilton cycles in prisms

Abstract: Abstract:The prism over a graph G is the Cartesian product G K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…Kaiser et al [9] attribute the following conjecture to Rosenfeld and Barnette [13]. It is implicit in [13] but does not seem to have been explicitly stated there.…”
Section: Introductionmentioning
confidence: 91%
“…Kaiser et al [9] attribute the following conjecture to Rosenfeld and Barnette [13]. It is implicit in [13] but does not seem to have been explicitly stated there.…”
Section: Introductionmentioning
confidence: 91%
“…Kaiser et al [10] trace this interest back to Barnette's famous open conjecture that the graphs of simple 4-polytopes are Hamiltonian. A related open conjecture posed by Rosenfeld and Barnette [15] claims that the prism of a 3-connected planar graph is Hamiltonian.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, another property sandwiched between "having a 2-tree", i.e., a Hamilton path, and "having a 2-walk" has attracted attention of researchers [10]. This property is that the prism of a graph is hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…We often identify one of the two copies of G in the prism with the graph G itself. It can be shown that if G has a Hamilton cycle, then its prism is hamiltonian and if its prism is hamiltonian, then G has a 2-walk [10]. Some old conjectures relaxed from "having a Hamilton cycle" to "having a hamiltonian prisms" become easy and some seem to remain still hard, e.g., it is not known whether there exists a constant k such that each k-tough graph has a hamiltonian prism (recall that a graph G is k-tough if, for every subset A of its vertices, G \ A is connected or has at most k|A| components).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation